The Gulf War Era Cohort and Biorepository: A Longitudinal Research Resource of Veterans of the 1990–1991 Gulf War Era. Issue 11 (30th July 2018) - Khalil, Lara; McNeil, Rebecca B; Sims, Kellie J; Felder, Kristina A; Hauser, Elizabeth R; Goldstein, Karen M; Voils, Corrine I; Klimas, Nancy G; Brophy, Mary T; Thomas, Catherine M; Whitley, Richard L; Dursa, Erin K; et al.
Abstract: The US Department of Veterans Affairs (VA) Gulf War Era Cohort and Biorepository (GWECB) is a nationally representative longitudinal cohort of US veterans who served during the 1990–1991 Gulf War era. The GWECB combines survey data, such as demographic, health behavior, and environmental exposure data; medical records; and a linked biorepository of blood specimens that can support a broad range of future research regarding health concerns unique to veterans of this era. To build this resource, the VA Cooperative Studies Program initiated a pilot study (2014–2016) to establish the GWECB and evaluate the processes required to build and maintain the resource. Participants ( n = 1, 275) consented to future sharing of their data and biospecimens for research purposes. Here we describe the pilot study, including recruitment and enrollment procedures, data collection and management, quality control, and challenges experienced. The GWECB data available to investigators under approved sharing mechanisms and the procedures for accessing them are extensively detailed. The study's consenting documents and a website link for the research survey are provided. Our hope is that new research drawing on the GWECB data and biospecimens will result in effective treatments and improved approaches to address the health concerns of Gulf War–era veterans.